2010
DOI: 10.3133/sir20105164
|View full text |Cite
|
Sign up to set email alerts
|

Breakpoint analysis and relations of nutrient and turbidity stressor variables to macroinvertebrate integrity in streams in the Crawford-Mammoth Cave Uplands Ecoregion, Kentucky, for the development of nutrient criteria

Abstract: To assist Kentucky in refining numeric nutrient criteria in the Pennyroyal Bioregion, the U.S. Geological Survey and the Kentucky Division of Water collected and analyzed water chemistry, turbidity, and biological-community data from 22 streams throughout the Crawford-Mammoth Cave Upland ecoregion (U.S. Environmental Protection Agency Level IV Ecoregion, 71a) within the Pennyroyal Bioregion from September 2007 to May 2008. Statistically significant and ecologically relevant relations among the stressor (total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…However, Miltner and Rankin (1998) found fish IBI scores in wadeable streams of Ohio significantly decreased at concentrations greater than 0.61 mg/L of TN, and Wang and others (2007) found a similar breakpoint for TN of around 0.60 mg/L. Crain and Caskey (2010) found multiple significant breakpoints between TP and invertebrate attributes between 0.032 and 0.035 mg/L in Kentucky.…”
Section: Management Implicationsmentioning
confidence: 92%
See 1 more Smart Citation
“…However, Miltner and Rankin (1998) found fish IBI scores in wadeable streams of Ohio significantly decreased at concentrations greater than 0.61 mg/L of TN, and Wang and others (2007) found a similar breakpoint for TN of around 0.60 mg/L. Crain and Caskey (2010) found multiple significant breakpoints between TP and invertebrate attributes between 0.032 and 0.035 mg/L in Kentucky.…”
Section: Management Implicationsmentioning
confidence: 92%
“…There tended to be a wide range of breakpoints in most of the biological communities. In previous studies in Wisconsin (Robertson and others, 2008), Indiana (Caskey and others, 2010), and Kentucky (Crain and Caskey, 2010) the mean or median of breakpoints from several relations were used to determine the appropriate breakpoint for a specific State or ecoregion. In our study, instead of averaging the significant breakpoints for attributes of each biological community, the breakpoints for each biological community were associated with either low nutrient concentrations indicative of lower trophic levels (oligotrophic) or high nutrient concentrations indicative of higher trophic (eutrophic) levels.…”
Section: Breakpoint Analysis Between Nutrients and Biological Attributesmentioning
confidence: 99%
“…(2013) in a review of stream nutrient criteria development in the U.S., which presented P threshold values of between 0.006 and 0.074 mg/L. This value was also greater than the biological breakpoint with median concentrations of TP (0.033 mg/L) observed by Crain and Caskey (2010). Bowes et al (2007) reported a threshold of 0.090 mg P/L on the River Frome in the UK.…”
Section: Threshold Soil M3p and Water Drp Valuesmentioning
confidence: 96%
“…Previous studies in nutrient enriched areas, such as the Central and Western Plains diatom ecoregion in the Midwest (Frey and others, 2011) and Wisconsin (Robertson and others, 2008), found low breakpoints for TP in the range of 0.075 to 0.088 mg/L. Several studies have identified low TP thresholds ranging from 0.025 to 0.040 mg/L based on modeled background concentrations (Robertson and others, 2006), the 33rd percentile of stream concentrations (Dodds and others, 1998), or breakpoint analysis in Kentucky (Crain and Caskey, 2010) and Wisconsin (Robertson and others, 2006). The mean low TP breakpoint threshold in this study was higher than those previously reported in the area.…”
Section: Major Findings and Implications For Developing Nutrient Critmentioning
confidence: 99%